Pengembangan Soft Skills Siswa Melalui Penerapan Culturally Responsive Transformative Teaching (CRTT) dalam Pembelajaran Kimia - Yuli Rahmawati; Achmad Ridwan; Sylvia Faustine; Pramita Cucu Mawarni (Postgraduate, University of Mataram, 2020)
This study aimed is to develop students’ soft skills through the implementation of the Culturally Responsive Transformative Teaching (CRTT) in chemistry learning. Indonesia's ethnic and cultural diversity is a challenge for teachers to design the chemistry lessons which is relevant with students’ characteristics. The research methodology applied is qualitative and applied on chemistry learning in the topics of acid and base, electrolyte and non electrolyte solution in five stages: self identification, cultural understanding, collaboration, critical reflections, and transformative construction. This research was conducted in two schools in DKI Jakarta and West Java in 2018. The data was collected by interview, reflective journal, and observations. The results showed that the chemistry learning through CRTT model can develop students' soft skills such as collaboration skills, critical thinking skills, nationality, social and cultural awareness, leadership, environmental caring, and curiosity. The teachers’ interview and reflections showed that the challenges in applying this approach were creativity in integrating cultural concepts in chemistry learning, students' understanding, time constraints, and the paradigm of students and teachers. Integration of ethnochemistry in CRTT can be developed in other chemical concepts with the principle of students’ character development